Collision in Brussels : the Common Market crisis of 30 June 1965 - Newhouse, John (W. W. Norton New YorkUS, 1967)
Deals with the European Economic Community's crisis of 1965 which paralyzed that institution, threatened the economy of Europe, and both caused and reflected political action throughout Europe. Annalyzes the political condition of Western Europe.